Tata ruang wilayah kerajaan Majapahit - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
There must to be sufficient justifiable supports, politically as well as economically, for Majapahit Kingdom, to stand for more than 200 years in East Java region